The Association between Earnings Management and Capital Structure: An Empirical Study on Jordanian Firms Listed in Amman Stock Exchange - Al-Mohareb, Manar; Alkhalaileh, Mahmoud (International Journal of Economics and Financial Issues, 2019)
The purpose of this study is to investigate the association between earnings management, measured by the absolute unexpected accruals and the firm’s capital structure. The study sample consists of 44 manufacturing Jordanian firms listed in the Amman Stock Exchange during the 5 years (2008-2012), a total of 220 (firm-year) observations. The study provides evidence supporting the hypothesized association between capital structure and the absolute unexpected accruals. Consistent with most prior related studies’ results, findings indicate a statistically positive association between earnings management and a firm’s financial leverage which is used as a proxy of the firm capital structure. This result hold for one measure of financial leverage (long–term-debt to equity ratio). However, when we use alternative leverage measure (total debt to assets ratio) as a capital structure proxy, the association between earnings management and leverage remains positive but statistically insignificant at the conventional level. Consistent with most related prior studies’ findings, the empirical evidence also shows that capital structure is negatively associated with profitability return on equity and positively related to firm size. The regression coefficients on both variables are statistically significant at the conventional level. Also, both external financing and investment opportunities, are positively and significantly associated with capital structure. Keywords: Earnings Management, Capital Structure, D/E Ratio, Unexpected Accruals, Profitability, Size, Amman Stock Exchange, Jordanian Firms JEL Classifications: G32, G15, M41 DOI: https://doi.org/10.32479/ijefi.8583